Screening before 24 weeks of gestation may be wise for early detection of abnormal glucose tolerance during pregnancy (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Screening for abnormal glucose tolerance (AGT) before 24 weeks of gestation (WG) is underestimated though its effects on pregnancy outcomes are not negligible.Objectives: To see the frequency of AGT before 24WG and its correlation with maternal risk factors.Methods: In this cross-sectional study, 451 pregnant women (gestational weeks 6-23) were enrolled from July 2013 to June 2017. Study participants underwent 75g OGTT (2 samples, n=451, 3 samples, n=249) to categorize them into normal glucose tolerance (NGT) or AGT following World Health Organization (WHO) criteria both 2013 and non-pregnant criteria. Glucose was measured by the glucose oxidase method.Results: Overt diabetes and prediabetes were 24 (5.3%) and 132 (29.3%) respectively when WHO non-pregnant adult criteria were applied (n=451). Whereas, 11 (4.4%) and 68 (27.3%) were diabetes in pregnancy (DIP) and gestational diabetes mellitus (GDM) respectively according to WHO 2013 criteria (n=249). Age (27.60±4.82 vs. 25.43±4.64, years, p